Developing a web-based initiation à la littérature française learning media using canva - Maryam Bajranata; Dadang Sunendar; Iis Sopiawati (Jurnal Inovasi dan Teknologi Pembelajaran, 2025)
In the rapidly evolving digital era, the need for effective, accessible, and technologically relevant learning media is increasingly demanding. Accordingly, this study aims to design and develop a web-based Initiation à la Littérature Française learning media using Canva and to provide information on the results of product feasibility in terms of materials and media. The method applied was Research and Development (R&D) with the PPE (Planning, Production, Evaluation) development model. In the data processing phase, this study conducted a validation test by two assessors—material expert judgement and media expert judgement based on the aspects developed by Nesbit & Li, 2009, LORI 2.0. The results reveal that from the material aspect, this learning media is very feasible to use, with a feasibility percentage of 86.1%, whilst from the media aspect, this product has a perfect feasibility of 100%. The finding implies that the web-based Initiation à la Littérature Française learning media using Canva is remarkably feasible.